ANALISIS KEBANGKRUTAN PERUSAHAAN SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yudi Agus Setiawan; Hakim Hakim; Wahyu Nur Himah (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2022)
This research aims to analyze bankruptcy condition in the PT. Bank J Trust Indonesia Tbk. The method of Altman Z-Score modification is used to know bankruptcy rate PT. Bank J Trust Indonesia Tbk on 2017-2019 period. The date used in this research is the bank’s annual financial report, after the company has published on the website of Indonesia Stock Exchange. The population in this research are all companies which listed on the Indonesia Stock Exchange, during the 2017-2019 period, while sample used is PT. Bank J Trust Indonesia Tbk financial report for the period 2017-2019 with purposive sampling method. The research result show that PT. Bank J Trust Indonesia Tbk during 3 year research period is in the “Distress zone” category, because has Z-Score under 1,10 (Z<1,10). With the respective Z-Score result in 2017, PT. Bank J Trust Indonesia Tbk was Z-Score -1,45, then Z-Score in 2018 was -1,83 and in 2019 was -1,4